Laporan Kasus : Teknik Pengukuran Derajat Keparahan Regurgitasi Aorta - Sinar, Claudia Arantha; Annisa, Fadila (ARKAVI [Arsip Kardiovaskular Indonesia), 2017)
Aortic regurgitation or aortic insufficiency is an abnormality in the aortic valve that becomes weak or enlarged so that the valve cannot close properly. It caused excessive amounts of blood in the left ventricle, which is received both from the left atrium and from the volume of aortic regurgitations through the incompetent aortic valve. It due to inadequacy of the aortic semilunar valve backflow of blood from the aorta into the left ventricle. Echocardiography is useful to determine cause of AR, by detecting the dilatation of the annulus and the aortic base, aortic dissection, or the primary of pathologic valve cusp. This case report aims to diagnose and determine the severity of Aortic Regurgitation with the PHT (Pressure Half Time) method on echocardiography. The results of the echocardiography examination showed an increased left ventricular thickness and mass accompanied by an increased left ventricular diastolic volume and pressure which can be called concentric LVH and aortic regurgitation. The results of this observation concluded that the techniques used in echocardiography have an effect on measuring the severity of aortic regurgitation. Keywords: Aortic Regurgitation, Echocardiography, Pressure Half Time